Iron deficiency anemia and its relationship with academic performance in university students - Quispe, Haydee (2021)
The objective was to know the level of iron deficiency anemia and its relationship that it exerts on the low academic performance of the students at the Professional School of Medical Technology of the Andean University Néstor Cáceres Velásquez de Puno-Peru (2019). The research was quantitative and descriptive, correlational, cross-sectional. The sample consisted of 53 students (women), who were from the I, II, III and IV semesters. To obtain data, the hemoglobin value of the students was determined, and a validated survey was applied to them to know their academic performance. The results showed that there are low percentages of students with iron deficiency anemia. The relationship, according to Spearman Rho, indicates that there is a moderate association between iron deficiency anemia and academic performance.